Atributos físicos e químicos de um argissolo sob diferentes Sistemas de Uso da Terra (SUTs) - Guidolini, Janaína Ferreira [UNESP] (2015)
The study of the transformations occurring in the soil due to the use and management is very important to choose the most appropriate system to regain ground potential. In order to evaluate the effect of different SUTs, physical quality and soil chemistry were analyzed for texture, macro and micro, total porosity, gravimetric moisture, bulk density, pH, CTC, H + Al, V%, Ca, Mg, MO, TOC, P and K. The SUTs analyzed were: native forest, reforestation with eucalyptus, agroforestry and pasture. Soil samples were collected in a Yellow Ultisol at the Polo Regional Centro Norte, city of Pindorama-SP at depths from 0.00 to 0.20 I 0.20 to 0.40 m. For this observation, is deformed composite samples (chemical and textural analysis) and soil samples (volumetric ring). Later, the data were statistically analyzed. Hierarchical cluster analysis was made and Principal Component Analysis (PCA). The soil of the native forest was used as a reference for comparison, because it is a system in balance and without human activity history. The physical attributes were satisfactory in all SUTs. Inadequate soil management are causing degradation of the same with respect to fertility, the studied systems. Multivariate analysis allowed the separation of SUTs